Value of vanin-1 assessment in adult patients with primary immune thrombocytopenia. (March 2014) - Elsalakawy, Walaa Ali; Ali, Mohamed A. M.; Hegazy, Marwa G. A.; Farweez, Botheina A. T.
Abstract The diagnosis of primary immune thrombocytopenia (ITP) is clinical and cannot be established by any specific laboratory assay. Perhaps the best diagnostic study is assessment of the patient's response to ITP therapy. Oxidative stress-related pathways were among the most significant chronic ITP-associated pathways. Overexpression of VNN1 gene, an oxidative stress sensor in epithelial cells, was most strongly associated with progression to chronic ITP. To address this issue, we tested the hypothesis that blood vanin-1 protein level could distinguish between chronic responders and non-responders ITP patients as well as between ITP patients and healthy controls. Vanin-1 protein levels were determined in peripheral blood leukocytes of 80 adult subjects (16 newly diagnosed ITP patients, 24 chronic responders ITP patients, 24 chronic non-responders ITP patients and 16 healthy controls) by enzyme-linked immunesorbent assay (ELISA). Blood vanin-1 protein levels were lower in controls (median = 18.39 ng) than in ITP patients (median = 58.78 ng) with a highly significant p value (p < 0.001). Vanin-1 levels were highly significantly elevated in newly diagnosed ITP patients (median = 188.62 ng) in comparison to chronic responders (median = 26.90 ng) and chronic non-responders (median = 73.87 ng). Vanin-1 level at a cut-off value of >20.73 ng was found to be 100% sensitive and 93.7% specific in discriminating between newly diagnosed ITP patients and healthy controls. Vanin-1 level was found to be 100% sensitive and 100% specific in differentiating between responders and non-responders with a cut-off value of ≤34.5 ng. Our results suggest that vanin-1 can distinguish between chronic responders and non-responders ITP patients as well as between newly diagnosed ITP patients and healthy controls. These findings demonstrate that vanin-1 may contribute to the pathogenesis of ITP, indicating that vanin-1 is an important target for further investigation.